Study on The Implementation of Environmental School Through Adiwiyata School Program on High School in The Halal Tourism Spots of East Lombok District - Windayani, Yuri; Surtani, Surtani (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
This study aims to analyze the study of the application of environmental schools through adiwiyata school program in high school in district of East Lombok. This type of research is qualitative. The subjects of this study were principals, teachers, and students. Research took place at SMAN 1 Montonggading and SMAN 1 Sambelia. Technique of collecting data through interview, observation, and also documentation. Data analysis used was data reduction, data presentation (display data), and conclusion. The results of this study indicated that: (1) in the aspect of the school's environment-oriented School Policy, there is no policy from the local government that the school is eligible to be an environmentally sound school (adiwiyata). (2) on the aspect of environmental-based curriculum content at the school there is no specific subject of PLH. (3) on the aspect of participative participatory environmental protection activities, there are several activities that support the development of environmental activities in SMA of East Lombok district based on participative. (4) on the aspect of school management in environmental management, it is still not maximal, (5). in the aspect of obstacles to the application of environmentally sound schools is the lack of understanding and knowledge of school residents about environmental education, cost and community support. (6). in the aspect of policy priorities that emerged in the changes is expected to analyze the obstacles in implementing environmental schools through the program of school adiwiyata through planning of learning tools by teachers compiled into the subjects of geography by integrating the maximum environmental values, the School makes environmental education as a optional subject, Development of geography teacher's knowledge and skills in collaboration with environmental agencies on environmental schools, and given understanding to the public about the importance of environmental education.